Deficiency of a leukocyte surface glycoprotein (LFA-1) in two patients with Mo1 deficiency. Effects of cell activation on Mo1/LFA-1 surface expression in normal and deficient leukocytes. - Arnaout, M A (1984)
Mo1, a phagocyte surface glycoprotein heterodimer, is involved in a number of phagocyte adhesion functions such as binding and ingestion of serum-opsonized particles, zymosan-induced degranulation, and superoxide generation. Deficiency of this antigen in humans has been associated with increased susceptibility to recurrent bacterial infections. The beta subunit of Mo1 is shared by another surface glycoprotein named LFA-1, which is involved in lymphocyte proliferation, cytolytic T cell, and natural killing activities. Two unrelated patients with Mo1 deficiency were found to be deficient in LFA-1 as well as in the common beta subunit. Investigation of lymphocyte functions in these two patients revealed normal mixed leukocyte culture-generated cytolytic T cell and natural killing activities and significantly reduced proliferative response to phytohemagglutinin. LFA-1-deficient cells also proliferated in response to soluble antigen and different alloantigens. These responses were partially blocked by anti-LFA-1 antibody. Whereas LFA-1 was undetectable by immunofluorescence and immunoprecipitation on the patients' resting T cells, significantly reduced (approximately 5% of normal) but detectable amounts of the heterodimeric LFA-1 antigen were found on mitogen and alloantigen-activated T cells. On granulocytes, Mo1 surface expression was also dependent on the state of cellular activation. The amount of surface Mo1 present on resting normal granulocytes increased by 3-10-fold following exposure to stimuli that induced degranulation, suggesting the presence of a major intracellular pool for this antigen. Analysis of subcellular fractions from granulocytes showed that intracellular Mo1 is located primarily in the specific granule fraction. Activated granulocytes had little or no increase in their surface expression of LFA-1 antigen. Deficient granulocytes had significantly increased numbers of Mo1 antigen expressed on the surface following stimulation with calcium ionophore (1 microM). However, the amount expressed continued to be significantly reduced compared with normal cells. Quantitation of surface Mo1 on granulocytes exposed to calcium ionophore (1 microM) showed that both parents in one family but only the mother in the other family had significantly reduced levels of Mo1, suggesting heterogeneity in the inheritance of this disorder. Whereas LFA-1 deficiency on lymphocytes was associated with normal alloantigen-induced cytolytic T cell and natural killing activities in these two patients, functions which were in part dependent on small amounts of detectable LFA-1 antigen, the Mo1 deficiency state led to significant defects in phagocyte adhesion functions. Hence, the clinical symptoms associated with this combined deficiency state reflect a more profound phagocyte than lymphocyte disorder.